2016
DOI: 10.1002/2016ja023346
|View full text |Cite
|
Sign up to set email alerts
|

Ionosphere data assimilation modeling of 2015 St. Patrick's Day geomagnetic storm

Abstract: The ionospheric plasma disturbances during a severe storm can affect human activities and systems, such as navigation and HF communication systems. Therefore, the forecast of ionospheric electron density is becoming an important topic recently. This study is conducted with the ionospheric assimilation model by assimilating the total electron content observations into the thermosphere‐ionosphere coupling model with different high‐latitude ionospheric convection models, Heelis and Weimer, and further to forecast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Chen et al . [, ] reported significant progress in reproducing storm time electron density and electric fields by assimilating TEC measurements with TIEGCM, and the root‐mean‐square error could be reduced by using rapid forecast cycles. They further showed that the assimilation results also provide much improved electric field forecast during quiet period by examining prereversal enhancement (PRE) of zonal electric fields [ Chen et al ., ].…”
Section: Plasma Bubble Inhibition Over Taiwanmentioning
confidence: 99%
See 4 more Smart Citations
“…Chen et al . [, ] reported significant progress in reproducing storm time electron density and electric fields by assimilating TEC measurements with TIEGCM, and the root‐mean‐square error could be reduced by using rapid forecast cycles. They further showed that the assimilation results also provide much improved electric field forecast during quiet period by examining prereversal enhancement (PRE) of zonal electric fields [ Chen et al ., ].…”
Section: Plasma Bubble Inhibition Over Taiwanmentioning
confidence: 99%
“…Figure 2 Recently, there have been several attempts to examine possible EPB generation on a given night by computing RTI growth rate by using TIEGCM data [Carter et al, 2014a[Carter et al, , 2014bWu, 2015], with the results showing overall good agreement between larger growth rate and bubble occurrence, though some discrepancies were also pointed out, especially in a study related to the St. Patrick's Day storm, which are attributed to the lack of physically meaningful representation of prompt penetration electric fields in the model [Carter et al, 2016]. Chen et al [2016aChen et al [ , 2016b reported significant progress in reproducing storm time electron density and electric fields by assimilating TEC measurements with TIEGCM, and the root-mean-square error could be reduced by using rapid forecast cycles. They further showed that the assimilation results also provide much improved electric field forecast during quiet period by examining prereversal enhancement (PRE) of Rajesh et al [2017], are plotted in Figure 3.…”
Section: Plasma Bubble Inhibition Over Taiwanmentioning
confidence: 99%
See 3 more Smart Citations